Efektivitas Program Ekstrakurikuler Tahfidz Al- Quran Dalam Pembentukan Karakter Religius Siswa: Studi Kasus di MTs TI Al Madani Pontianak - Nia Hasanah; Muhammad Agus Salim; Muhammad Zaironi (Jurnal Al-Fatih, 2026)
This study aims to describe the implementation of the extracurricular Tahfidz Juz 30 program in shaping the religious character of students at MTs TI Almadani. The study used a qualitative approach with a descriptive approach. Data were obtained through observation    the Tahfidz instructor and students as data sources. The results indicate that the extracurricular Tahfidz Juz 30 program is implemented on a weekly schedule and utilizes various learning methods, including wahdah, kitabah, sima'i, jama', talaqqi, tafsir, and tajwid. This program not only focuses on improving Quran memorization skills but also plays a role in shaping students' religious character through habituating Quran reading, enhancing discipline, responsibility, and adherence to religious practices. Program evaluation is conducted through tasmi' activities at the end of each semester to measure students' fluency, recitation accuracy, and memorization quality. Evaluation results indicate that the tahfidz program has a positive impact on students' Quran memorization abilities and the development of their religious character. Thus, the extracurricular tahfidz program for Juz 30 at MTs TI Almadani contributes to improving the quality of Quran memorization while supporting the development of students' religious character.